Polarization misalignment between signal and crosstalk in direct detection WC-MCF systems - Alves, T. M. F.; Cartaxo, A. (IEEE Photonics Technology Letters, 2023)
The impact of the polarization misalignment between the signal and the intercore crosstalk (ICXT) on the performance of direct detection (DD) weakly coupled multicore fiber (WC-MCF) systems is investigated by numerical simulation. It is shown that the bit-error ratio (BER) is not maximized for all time when the signal field polarization is aligned with the polarized component of the ICXT. However, this is the scenario in which higher levels of bit-error ratio (BER) occur more frequently along time. For the same outage probability, these higher BER levels lead to an incremental requirement of the ICXT level between 1 dB and 2 dB when compared with the scenario of independent polarizations of the signal and ICXT fields. These conclusions are valid for on-off-keying DD WC-MCF short-reach systems operating with arbitrary product between the skew (i. e., the relative propagation time delay between two cores) and the bit rate.